2018
DOI: 10.1007/s10695-018-0496-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary organic, inorganic, and nanoparticulate selenium sources on growth, hemato-immunological, and serum biochemical parameters of common carp (Cyprinus carpio)

Abstract: An 8-week feeding trial was conducted to compare the effects of supplementing (0.7 mg kg) different dietary selenium (Se) sources including organic [selenomethionine (SeMet)], inorganic [sodium selenite (NaSeO)], and nanoparticulate Se (nano-Se) on physiological responses of common carp, Cyprinus carpio juveniles (9.7 ± 0.1 g). Basal diet without Se supplementation used as control. Fish fed nano-Se supplemented diet had the highest weight gain (97.2 ± 10.8%) and feed efficiency ratio (42.4 ± 0.8%). Intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 47 publications
9
49
1
Order By: Relevance
“…A serum concentration of MDA is an index of lipid peroxidation and oxidative stress, and its levels depend upon the antioxidants (Saffari et al, 2018). In present findigs regarding antioxidant status, plasma MDA decreased with the supplementation of Se-yeast and Se-algae.…”
Section: Plasma Constituents and Blood Antioxidative Statusmentioning
confidence: 50%
“…A serum concentration of MDA is an index of lipid peroxidation and oxidative stress, and its levels depend upon the antioxidants (Saffari et al, 2018). In present findigs regarding antioxidant status, plasma MDA decreased with the supplementation of Se-yeast and Se-algae.…”
Section: Plasma Constituents and Blood Antioxidative Statusmentioning
confidence: 50%
“…These results suggest that the combination of NanoSe and NanoMg may improve the immune response of Asian seabass. Similarly, dietary NanoSe supplementation led to an increase in ACH 50 in common carp (Saffari et al, ) and red sea bream (Dawood et al, ). Moreover, Wang et al () demonstrated that administration of Mg‐supplemented diets can enhance the non‐specific immunity in juvenile grass carp.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Se nanoparticle (NanoSe), a novel Se form, has attracted considerable attention, due to its higher bioavailability and relatively low toxicity compared to other Se sources (Hu et al, ; Rezvanfar et al, ; Shi et al, ; Wang, Yan, & Fu, ). Several authors showed that dietary supplementation with NanoSe could improve growth performance, antioxidant defence system, immune response and muscle Se content in fish species studied (Ashouri, Keyvanshokooh, Salati, Johari, & Pasha‐Zanoosi, ; Dawood et al, ; Naderi, Keyvanshokooh, Salati, & Ghaedi, ; Saffari, Keyvanshokooh, Zakeri, Johari, & Pasha‐Zanoosi, ; Saffari et al, ; Zhou, Wang, Gu, & Li, ). Also, Mg nanoparticle as a feed additive has been reported to have antibacterial and antioxidative effects (Manuel y Keenoy et al, ; Tang & Lv, ).…”
Section: Introductionmentioning
confidence: 99%
“…Se as an essential nutrient for fish has been researched in many fish species, including grass carp (Liu et al, , ; Saffari, Keyvanshokooh, Zakeri, Johari, & Pasha‐Zanoosi, ; Xia et al, ; Zhou, Wang, Gu, & Li, ). Se nanoparticle (Nano‐Se) is the novel Se form and has attracted remarkable attention, as it exhibits higher bioavailability, lower toxicity and strong bioactivity in comparison with inorganic and organic Se (Saffari et al, , ; Zhou et al, ). Zhou et al () showed that Nano‐Se are more efficient in increasing muscle Se content compared to organic Se (selenomethionine, SeMet) in the crucian carp (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…is the novel Se form and has attracted remarkable attention, as it exhibits higher bioavailability, lower toxicity and strong bioactivity in comparison with inorganic and organic Se (Saffari et al, 2017(Saffari et al, , 2018Zhou et al, 2009). Zhou et al (2009) showed that Nano-Se are more efficient in increasing muscle Se content compared to organic Se (selenomethionine, SeMet) in the crucian carp (Zhou et al, 2009).…”
mentioning
confidence: 99%